Sosialisasi Google Family Link Sebagai Sarana Pengawasan Penggunaan Gawai Pada Anak : Sosialisasi Google Family Link Sebagai Sarana Pengawasan Penggunaan Gawai Pada Anak - Aded Rifaldy; Bintang Mahesa Nugraha; Muhamad Pahmil Mahdi; Khalil Gibran Almaulidi; Ednas Prasetio; Muhamad Buge Mahara; aditya wardhana (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The introduction of technology or gadgets to children is not wrong, but it is hoped that the role of parents is to participate in supervising the use of gadgets in children. The use of gadgets without supervision has several negative impacts on social interaction such as they are more comfortable using gadgets than interacting or playing with their peers. However, there is also a positive influence on the introduction of gadgets to children, such as being able to hone cognitive abilities, learn to be responsive to technology and think more creatively. The introduction of technology/gadgets to children is not wrong, but it is hoped that the role of parents is to participate in supervising the use of gadgets in children.